Quasi-two-dimensional Brownian dynamics simulations on the local internal structure of a cubic magnetic particle suspension in an alternating magnetic field - Kazuya OKADA; Akira SATOH (Nihon Kikai Gakkai ronbunshu, 2022)
In the present study, we have addressed a dispersion composed of magnetic cubic particles in an alternating magnetic field to investigate the time change in the local internal structure of particle aggregates by means of quasi-two-dimensional Brownian dynamics simulations. An alternating magnetic field is applied along the x-direction. In the situation of a relatively weak magnetic field, if the magnetic particle-particle interaction strength is small, single particles remain in the system. The magnetic moments of single particles follow the change in the switched direction of the alternating magnetic field. As the magnetic particle-particle interaction strength is increased, particles aggregate to form closely-packed structures with a perfect face-to-face configuration. Since the orientation of the magnetic moments of constituent particles is strongly restricted due to the influence of the magnetic particle-particle interaction between neighboring particles, they do not follow the change in the alternating magnetic field direction. As the magnetic particle-field interaction strength is increased, closely-packed structures tend to collapse, and loosely-packed structures are formed in the system. As the magnetic particle-field interaction strength is further increased, the magnetic moments of constituent particles are restricted to the direction of the alternating magnetic field. Therefore, the aggregates with an offset face-to-face configuration are formed along the magnetic field direction. If the alternating magnetic field switches from the positive x-direction to the negative x-direction, the aggregates with an offset face-to-face configuration collapse temporarily because the magnetic moments reorient in the switched direction of the alternating magnetic field. After that, the orientation of the magnetic moments is strongly restricted to the switched magnetic field direction, and aggregates with an offset face-to-face configuration are re-formed in the system.